(3ESeGY GdUe aj EKHGJ GdTQa ef bHd GdCes - (3CHh YHO Gddg eMeO Hf RjO (B( (3Ch jRjO(B) (3GdeQGcTi GdVQjQs; (3CHh YHO Gddg eMeO Hf YHO GdQMef GHf CHh RjO GdeQGcTj, GdVQjQ,J (B807 (3g` s
(3ChdgG (B:s
(3GeG HYO aEf HYV fTC GUd HfhJg eef NUg Gddg HSHYG s
(3BNQgG (B:s
(3RQVi Gddg Yfge hYf LejY UMHge s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B193s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B247 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe LRA (B2/ 1 - (3U (B17 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs